Seed mucilage content in Aethionema W.T. aiton species and their significance in systematic and ecological aspects - Karaismailoglu, Mehmet Cengiz (Bangladesh Journal of Botany, 2018)
The seeds of the seven Aethionema taxa, namely A. syriacum (Boiss.) Bornm., A. froedinii Rech., A. arabicum (L.) Andrz. ex DC., A. speciosum Boiss. et Huet. subsp. speciosum, A. saxatile (L.) R. Br., A. armenum Boiss. and A. grandiflorum Boiss. et Hohen. were found to have mucilage cells on the surface, and they produce a slippery liquid during hydration. The mucilage in the examined taxa consisted of the pectin or cellulose. Mucilage cells were found to have different anatomical layers in seeds. Moreover, there were differences in columellae shapes in Aethionema taxa, which are prominent, flattened or reduced shapes. In addition, soil adhesion capacities of the taxa ranged from 28 to 356 mg. The presence of mucilage can play a key role in seed dispersion and colonization for the new habitat in Aethionema taxa.